Firm level productivity under imperfect competition in output and labor markets - Sara Amoroso; Peter M. Kort; Bertrand Melenberg; Joseph Plasmans; Mark Vancauteren (Center for Economic Studies and ifo Institute (CESifo), 2010)
This article examines the role of the interaction between product market and labor market imperfections in determining total factor productivity growth (TFPG). Embedding Dobbelaere and Mairesse's (2009) generalization of Hall's (1990) approach, allowing for the possibility that wages are determined according to an efficient bargaining process between employers and employees, we correct estimated TFPG for possible biases arising from labor market imperfections. Our analysis contributes to the literature in a number of ways. First, we propose a new empirical measure of TFPG which takes into account possible biases coming from imperfect competition on both labor and output markets, whereas Dobbelaere and Mairesse (2009) focus on the decomposition of the Solow residual. Second, in contrast to most of the literature following Hall's approach, we estimate market power including the user cost of capital stock. Third, we measure the sensitivity of TFPG to an alternative specification of competition based on relative profits. Using a large Dutch firm-level panel database over the period 1989-2005, we find that workers' unions power, and in general rigidities of the labor market, affect firms' marginal cost, and, consequently, the markups. Moreover, taking into account variable returns to scale and imperfect competition in the output market translate into increased TFPG, while accounting for labor market bargaining power leads to lower TFPG. Next, the investigation of our empirical relationship between the price-cost margin and an alternative specification of imperfect competition of the output market (profit elasticity) as a sensitivity analysis of the TFPG shows that adding more structure to the competition measure does not affect the level of productivity change.
Keywords: D21; D24; L00; L13; 330; Produktivität; Panel; Schätztheorie; Unvollkommener Wettbewerb; Arbeitsmarkt; Unvollkommener Markt; Theorie; Schätzung; Niederlande